2021
DOI: 10.1007/s11266-021-00373-3
|View full text |Cite
|
Sign up to set email alerts
|

All Earned Revenue is Not Created Equal: Revenue Embeddedness as a Framework for Exploring Crowding-In/Crowding-Out Effects

Abstract: of SAS, Institute for their gracious assistance.Robust regression analysis provides an alternative to a least squares regression model when fundamental assumptions are unfulfilled by the nature of the data. When the analyst estimates his statistical regression models and tests his assumptions, he frequently finds that the assumptions are substantially violated. Sometimes the analyst can transform his variables to conform to those assumptions. Often, however, a transformation will not eliminate or attenuate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Hung (2020) performed a meta-analysis on the relationship between commercialization and private donations, finding that commercialization and private donations were not related in cultural nonprofit organizations -again in studies that were largely from the United States, United Kingdom and Canada. Examining earned revenue activities, Levine Daniel (2021) showed that earned revenue activities complement donations when the activity entails offering new products or services to existing donors.…”
Section: Fundraising: If You Don't Ask You Don't Getmentioning
confidence: 99%
“…Hung (2020) performed a meta-analysis on the relationship between commercialization and private donations, finding that commercialization and private donations were not related in cultural nonprofit organizations -again in studies that were largely from the United States, United Kingdom and Canada. Examining earned revenue activities, Levine Daniel (2021) showed that earned revenue activities complement donations when the activity entails offering new products or services to existing donors.…”
Section: Fundraising: If You Don't Ask You Don't Getmentioning
confidence: 99%